2018
DOI: 10.1016/j.ijbiomac.2018.09.180
|View full text |Cite
|
Sign up to set email alerts
|

RK, the first scorpion peptide with dual disintegrin activity on α1β1 and αvβ3 integrins

Abstract: the first scorpion peptide with dual disintegrin activity on α1β1 and αvβ3 integrins. Abstract:Scorpion peptides are well known for their pharmaceutical potential on different targets. These include mainly the ion channels which were found to be highly expressed in many diseases, including cancer, auto-immune pathologies and Alzheimer. So far, however, the disintegrin activity had only been characterized for snake venom molecules. Herein, we present the first short peptide, purified from the venom of Buthus oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Integrin antagonists comprise molecules that can bind and interfere with the activity of the cellular receptors integrins. Some proteins or peptides are found in snake venoms such as the C-type lectins EMS6 ( Marcinkiewicz et al, 2000 ) and Vixapatin ( Momic et al, 2012 ) or disintegrins ( Calvete, 2005a ), or found in other animals venoms such as arthropods ( Khamessi et al, 2018 ). The snake venom disintegrin family comprises a group of cysteine-rich proteins (40–100 amino acids) found in the venom from snakes from Elapidae, Viperidae, Atractaspididae, and Colubridae families ( Kini and Evans, 1992 ; Calvete et al, 2005b ; Arruda Macedo et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Integrin antagonists comprise molecules that can bind and interfere with the activity of the cellular receptors integrins. Some proteins or peptides are found in snake venoms such as the C-type lectins EMS6 ( Marcinkiewicz et al, 2000 ) and Vixapatin ( Momic et al, 2012 ) or disintegrins ( Calvete, 2005a ), or found in other animals venoms such as arthropods ( Khamessi et al, 2018 ). The snake venom disintegrin family comprises a group of cysteine-rich proteins (40–100 amino acids) found in the venom from snakes from Elapidae, Viperidae, Atractaspididae, and Colubridae families ( Kini and Evans, 1992 ; Calvete et al, 2005b ; Arruda Macedo et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%